Konsekuensi Hukum bagi Pejabat Negara yang Terbukti Melakukan Tindak Pidana Pencucian Uang dalam Sistem Hukum Pidana Indonesia - Listiana, Cici Ayu; Karli, Karli (LPPM Iblam School of Law, 2024)
Tindak pidana pencucian uang (TPPU) is a severe crime that threatens the stability of Indonesia’s economic and legal system. The involvement of state officials in TPPU not only undermines public trust but also weakens the integrity of governmental institutions. This study analyzes the legal consequences for state officials proven to be involved in money laundering within Indonesia’s criminal law framework. The research aims to provide a comprehensive understanding of sanctions and legal enforcement mechanisms applicable to corrupt officials. This study employs a qualitative approach with a normative legal method, focusing on regulatory analysis and the interpretation of legal norms in practice. Data collection relies on literature studies involving primary legal sources such as laws, regulations, and court decisions, complemented by secondary sources like legal books and academic journals. The findings indicate that state officials convicted of TPPU face severe criminal penalties, including imprisonment, fines, dismissal from office, and future restrictions from holding public positions. However, legal enforcement faces significant challenges, including political intervention, sophisticated money laundering methods, and resource limitations. Strengthening regulatory frameworks, improving inter-agency coordination, and enhancing public transparency are crucial steps in addressing this issue. This study underscores the need for multi-sectoral efforts to ensure effective law enforcement and restore public confidence in governance